Forecasting the Occurrence of Rainfall in Selected Weather Stations in the Wet and Dry Zones of Sri Lanka - Perera, H.K.W.I.; Sonnadara, D.U.J.; Jayewardene, D.R. (My University, 2002)
Two models were developed based on the Markov method to predict the occurrence of rainfall. Daily rainfall data from 9 meteorology stations in Sri Lanka namely, Colombo, Ratnapura, Kandy, Galle, Hambanthota, Batticaloa, Anuradhapura, Badulla and Trincomalee were analysed using these models. The results show that the models can forecast the status of a given day at an average of 73%. Higher agreement is seen for stations in the dry zone of Sri Lanka when compared with those in the wet zone. No significant difference was observed between the results obtained using the 1st order Markov process and the 2nd order Markov process. The models were not sensitive to the range of data used or the short-term fluctuations.
Keywords: Rainfall; Weather; Wet and Dry Zones